Nonclassical photon correlation of nanoparticle in a microcavity - Ooi, Chong Heng Raymond; Gong, Q.H. (American Physical Society, 2012)
We study the quantum correlation of photon pairs from a double Raman particle driven by laser fields in a modified photon density of states such as a cavity or a defect in a photonic crystal. We obtain an exact semianalytical expression for the photon correlation, which is characterized by two complex decay functions associated with the levels splitting (effective Rabi frequencies) that depend on the control laser field. The position and width of the cavity density of state with respect to the anti-Stokes transition determine the features in the two-photon correlation profile.